1983
DOI: 10.1002/kin.550150206
|View full text |Cite
|
Sign up to set email alerts
|

Relative rate constants for removal of vibrationally excited OH(X2πi)v=9 by some small molecules at room temperature

Abstract: Vibrationally excited OH in u = 9 [designated OHf(9)] was generated by the reaction of hydrogen atoms with ozone in a fast-flow discharge system at 300 f 3 K and a total pressure of 1.1 f 0.1 torr, with argon as the carrier gas. The addition of a species X, which can deactivate the OHt(9) or react with it, led to a decrease in the Meinel band chemiluminescent emission intensities at both 626 nm (9 -3 band) and 519 nm (9 -2 band), which were monitored as a function of the concentration of X. Application of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Under local thermodynamic equilibrium conditions, the fraction of vibrationally excited molecules is in the order of magnitude of only 10 −8 . Literature on the rate coefficients involving Reaction (R1) for vibrationally excited OH is quite sparse and in partial disagreement (Coltharp et al, 1971;Worley et al, 1972;Finlayson-Pitts et al, 1983;Varandas and Zhang, 2001 and references therein). For our study, rate coefficients as a function of temperature and OH vibrational level as suggested by Varandas and Zhang (2001) are used.…”
Section: Introductionmentioning
confidence: 99%
“…Under local thermodynamic equilibrium conditions, the fraction of vibrationally excited molecules is in the order of magnitude of only 10 −8 . Literature on the rate coefficients involving Reaction (R1) for vibrationally excited OH is quite sparse and in partial disagreement (Coltharp et al, 1971;Worley et al, 1972;Finlayson-Pitts et al, 1983;Varandas and Zhang, 2001 and references therein). For our study, rate coefficients as a function of temperature and OH vibrational level as suggested by Varandas and Zhang (2001) are used.…”
Section: Introductionmentioning
confidence: 99%